Marriage or celibacy? : the Daily telegraph on a Victorian dilemma - Robson, John M. (University of Toronto Press, 1995)
In July 1868 the Daily Telegraph congratulated itself on providing the arena for a controversy marked by "good sense, liveliness, practical wisdom, and hearty humanity." The controversy was over the choice - "Marriage or Celibacy?"--Faced by middle-class youth trying to reconcile economic facts with moral values, social customs - and love. The arena was the correspondence page of a newspaper just establishing itself as the most successful London daily through its appeal to the middle-class reader.